Grayscale Digital Light Processing and Post‐Treatment for the Fabrication of 3D‐Printed Polymer Blends. Issue 8 (5th February 2022) - Hergert, John E.; Uzcategui, A. Camila; Muralidharan, Archish; Crespo-Cuevas, Victor; Ferguson, Virginia L.; McLeod, Robert R.
Abstract : 3D‐printed polymer blends with programmable mechanical and compositional heterogeneity were fabricated using grayscale digital light processing by spatially modulating the intensity of light during printing and swelling the resulting part with a second monomer. A rubbery poly(ethylene glycol) diacrylate functionally graded print is variably swollen with acrylamide monomer as a function of crosslinking density. Following a secondary polymerization, a 3D‐printed functionally graded blend with regions of varying composition and stiffness was formed. A deterministic model for polymer conversion informs printing conditions to correspond with predicted material properties based upon local volume fractions of the two materials. Upon the secondary polymerization, two networks are present within the printed structure including glassy and rubbery regions. The compressive moduli of local regions within prints ranges from 76 to 200 MPa and measured moduli of the structures agree with predicted values acquired using finite element analysis. A lattice structure with prescribed local stiffness printed using grayscale exposures deforms differentially when compressed. Advantageously, local dimensional deformations caused by the removal of the unreacted printing monomer are eliminated due to the introduction of the second polymer. This method provides predictive control over local mechanical properties and high shape precision while maintaining the simplicity of vat photopolymerization. Abstract : 3D‐printed polymer blends with programmable mechanical heterogeneity are fabricated using grayscale digital light processing by spatially modulating the intensity of light during printing, followed by swelling the part with a second monomer. A predictive model for local mechanics is established, thus predictive control over mechanical properties and high shape precision are achieved while maintaining the simplicity of vat photopolymerization.